The concepts of «biographica» and «biographistica» in Russian, Ukrainian and Belarusian historical science - Nastusevich, Stanislav V. (Journal of the Belarusian State University. History, 2022)
The article covers the history of emergence and practice of using the concepts of «biographica» and «biographistica» in Russian, Ukrainian and Belarusian historical science. The theoretical discussions that took place in Soviet historical science on issues of the biographical genre are examined. The major versions of appearance of the abovementioned concepts are given and analysed. The major meanings intended by Russian, Ukrainian and Belarusian researchers is revealed through the analysis and comparison of the practice of using these concepts. The author’s vision of the subject of the discipline of biographica (biographistica) is presented. Three of its major directions within the established disciplinary system of social and humanitarian sciences are distinguished: philosophical, literary-artistic, historical. The definition of the concept of «historical biographica» is given.